Pathogenesis of Severe Clinical Pictures of Influenza A (H1 N1). Some answers and new doubts. - Alfredo Darío Espinosa Brito; Ángel Julio Romero Cabrera (Medisur)
One of the main characteristics of the current pandemic caused by the virus of Influenza A (H1N1) is the presence of non-habitual groups of high risk to develop severe clinical pictures, mainly as a consequence of a complicated serious pneumonia associated to an adult respiratory distress syndrome. This situation may lead the patient to the intensive care unit and could cause his death, although the figures of such cases stay relatively low, in relation to other epidemics of seasonal Influenza. Among those groups are the people between the ages of 10 and 60 years, seemingly healthy, pregnant and postpartum women, and obese and asthmatic patients, but until now a specific medical comorbidity has not been evidenced in the 40 to 50% of the fatal cases. In this work we offer possible answers to why these groups of risk suffer from severe complications of the illness, starting from an analysis of the triad: agent-guest-environment. A group of ideas obtained from the review of medical literature are exposed plus the clinical experience of the authors in the medical care of those sick persons. It is emphasized the necessity of early identification of high risk patients of presenting severe complications, mainly those "hyperimmunes", that we can be able to manage them. It is emphasized that new answers originate new questions. Meanwhile, the whole diagnosis and therapeutic’s arsenal for the prevention and the care of the critical sick persons, should be put on at the patients’ disposition, especially to those ones that required intensive care.